Salvadoran higher education: access to tertiary system, budget constraints and Faculty Academic quality, 1980-2002 - Pérez Hernández, Mercy Carolina (Universidad de El Salvador, 2003)
For many years El Salvador has struggled to provide its people with tools that can help them to face the challenges of a changing and globalized world, and one of these tools is education, since it is one means by which a country can reach a level of educational and economic competitiveness that allows its integration to world development and offer its citizens a better life style. As the World Bank in its “World Development Report 1999/2000” says, “Education thus contributes, within the context of a sound macro-economic and political environment, to the entire society’s growth and development, which in turn raises incomes for all. A good education system is a necessary but insufficient condition for development, and its benefits are strongest when crucial other areas of public policy are equally well managed”. This essay is argumentative, and descriptive since it aims to point out the main problems that Salvadoran Higher Education has faced since 1980 up to 2002, and which still have not been overcome, such as budgets constraints, access and academic faculty quality. Because despite changes have been carried out on quality of Higher Education, they have not been enough to contribute to the social and economic development of El Salvador.